Variability in Certainty of Self-Reported Interest: Implications for Theory and Research: Implications for Theory and Research - Durik, Amanda; Jenkins, Jade (Frontline Learning Research, 2020)
These studies examined self-reported interest, how level of interest is related to reported certainty of interest, and whether certainty helps to clarify the relationship between interest and behavior. This research borrows from research on attitudes showing that attitude certainty helps to clarify the relationship between attitudes and behavior. A pilot study examined the relationship between self-reported interest and certainty of interest within four disciplines (math, psychology, biology, and astronomy). These relationships were replicated in math (Study 1) and psychology (Study 2), and the relationships between interest and behavior were stronger for those with greater certainty. For domains in which participants had sufficient levels of experience and varied levels of interest, curvilinear relationships were found between level of interest and certainty, showing that certainty is higher among individuals who report more extreme (high or low) levels of interest. Moreover, self-reported interest predicted behavior more strongly for those with more certainty in their responses. Discussion surrounds the theoretical and methodological utility of considering certainty of interest alongside measures of self-reported interest.